On‐Chip Integration of Single Photon Sources via Evanescent Coupling of Tapered Nanowires to SiN Waveguides. Issue 2 (17th May 2019) - Mnaymneh, Khaled; Dalacu, Dan; McKee, Joseph; Lapointe, Jean; Haffouz, Sofiane; Weber, John F.; Northeast, David B.; Poole, Philip J.; Aers, Geof C.; Williams, Robin L.
Abstract: A method to integrate nanowire‐based quantum dot single photon sources on‐chip using evanescent coupling is demonstrated. By deterministically placing an appropriately tapered III‐V nanowire, containing a single quantum dot, on top of a silicon‐based ridge waveguide, the quantum dot emission directed toward the taper can be transferred to the ridge waveguide with calculated efficiencies close to 100%. As the evanescent coupling is bidirectional, the source can be optically pumped in both free‐space and through the ridge waveguide. The latter configuration paves the way toward a self‐contained, all‐fiber, plug‐and‐play solution for applications requiring a bright on‐demand single photon source. Using InAsP quantum dots embedded in InP nanowire waveguides, coupling efficiencies to a SiN ridge waveguide of 74% with a single photon purity of 97% are demonstrated. The technique to demonstrate deterministic placement of single quantum emitters onto pre‐fabricated waveguides is used, an important step toward the fabrication of complex quantum photonic circuits. Abstract : Nanowires with tailored tapers are used to demonstrate evanescent coupling of the fundamental nanowire mode to an underlying ridge waveguide with a measured coupling efficiency of 74%. Using a single quantum dot embedded in the nanowire, on‐chip single photon emission is demonstrated with a single photon purity of 97%.